المعالجة الكيميائية لعسارة المياه الجوفية حالة دراسة: مياه الآبار في محافظة حماه / سوريا- - السلوم درغام; عوض عادل; النيربيه مي (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف البحث إلى إيجاد أفضل الشروط الممكنة لمعالجة عسارة المياه الجوفية كيميائياً ، وذلك باستخدام محاليل كيميائية منفردة أو بشكل مجموعات منها ، في محطة معالجة مصغرة رائدة جرى تصميمها وتصنيعها لهذا الغرض. وقد تضمنت الدراسة استخدام محاليل الكلس وكربونات الصوديوم وكلوريد الحديد والنشاء في معالجة مياه بئر في محافظة حماه. وقد أرشدت هذه الدراسة تجريبياً إلى فائدة جمع كربونات الصوديوم مع الكلس في هذه المعالجة والنسب المثلى لها ، وإمكانية الاستفادة من كلوريد الحديد والنشاء عند إضافتها إلى كربونات الصوديوم والكلس في هذه المعالجة. This research tries to find the best conditions for the chemical treatment of the groundwater hardness, using four different chemical solutions, individually or in combinations, in a small pilot treatment plant specially designed for this purpose. The study includes the use of solutions of lime, sodium carbonate, ferric chloride and starch in the treatment of one of the wells in Hama Governorate. It indicates experimentally that the use of a combination of lime and sodium carbonate in this treatment is advantageous, and the ideal ratios of the two chemicals are determined for the different ranges of doses. The study shows also the possibility of adding ferric chloride and starch solutions to those of lime and sodium carbonate to improve the results.